Analysis on Deformation and Stress Characteristics of a Multibraced Pit-in-Pit Excavation in a Subway Transfer Station - Xin Shi; Chuanxin Rong; Hua Cheng; Linzhao Cui; Bin Wang; Shicheng Sun (Advances in Civil Engineering)
As an important part of subway transfer station construction, pit-in-pit (PIP) excavation has always been a key object of monitoring and control. In this study, taking the PIP excavation project of Hefei metro line 4 and line 7 transfer station as the background, combined with on-site monitoring and numerical simulation, the variation law of lateral wall displacement, ground surface settlement, and strut force during the PIP excavation were analyzed. The results showed that the maximum lateral deformation of the pile caused by the excavation of the external pit accounted for 80%–90% of the total deformation and the surface settlement accounted for 70% of the total settlement. The excavation of the inner pit only made the maximum lateral wall displacement of the outer pit and the surface settlement behind the wall increase slightly, the growth rate tended to zero, and the maximum lateral deformation depth was all above the excavation surface, which indicated that, for this project, the inner excavation had little effect on the outer pit retaining structure. In addition, the increased exposure time of the soil at the bottom of the pit and the presence of the corner effect will cause the further development of the structure displacement and the surface settlement. Based on strut force measurements, using the tributary area load distribution procedure, it was obtained that 0.3γHe was used as the upper limit index of strut force in the region, where γ is the weight of the soil and He is the excavation depth of the foundation pit. The research conclusions were helpful for the construction and sustainable development of the PIP project.